Réponse écophysiologique de l'huître creuse Crassostrea gigas à la variabilité spatio-temporelle des facteurs environnementaux. Etude par modélisation écologique - Grangere, Karine (Université de Caen Basse-Normandie, 2009)
The spatial and temporal variability in biotic and abiotic environmental factors influence the ecophysiological response of bivalves (growth, reproduction and survival). In this study, the physiological status of cultivated oysters in the Baie des Veys ecosystem was studied using an ecosystem model which simulates ecophysiological processes of oysters (growth, maintenance and reproduction) and environmental processes which control oyster responses (river inputs, meteorology, hydrodynamic). In order to assess the spatial and temporal scales of variability in this ecosystem, two modelling approaches were developed. Temporal variability from the seasonal to the inter-annual scale was studied using a box model. Results showed that the variability in terrestrial inputs (nutrient, suspended particulate matter) has an influence on phytoplankton dynamics and consequently on oyster growth patterns. Spatial variability was assessed using a hydrodynamic model. Results highlighted that cultivated oyster density, immersion time and current velocity are the main factors controlling the availability of food and consequently spatial heterogeneity of oyster growth at the cultivation scale. The ecophysiological response of oysters to the spatio-temporal variability in environmental factors was studied using an indicator of the ecophysiological status based on energy needs. Results obtained are discussed in relation to oyster summer mortality events recorded in this ecosystem. La variabilité spatio-temporelle des facteurs environnementaux biotiques et abiotiques influence la réponse écophysiologique des bivalves (croissance, reproduction et survie). Dans cette étude, l'état physiologique des huîtres cultivées dans la Baie des Veys a été analysé par la mise en place d'un modèle d'écosystème intégrant les processus écophysiologiques de l'huître (croissance, maintenance et reproduction) et les processus environnementaux qui contrôlent les réponses de l'huître (apports terrigènes, météorologie, hydrodynamisme). Afin d'appréhender ...